Improved AB-CPREs with Revocability and HRA Security under LWE - Yang Wang; Mingqiang Wang (IET Information Security)
Attribute-based conditional proxy re-encryption protocols (AB-CPREs) enable a delegator to delegate his decryption rights via different policies and grant the data owner greater flexibility in allocating their encrypted private data stored in the cloud. However, existing lattice-based AB-CPREs suffer from some drawbacks such as large parameters and weak passive securities. To the best of our knowledge, the first quantum-safe key-policy AB-CPREs with polynomially bounded parameters (for certain NC 0 circuits/policies) that is selective attribute secure against honest re-encryption attacks (HRA) is presented. The security of our proposed AB-CPREs is based on standard LWE assumptions. We further introduce the directly revocable AB-CPREs, a primitive that enables a delegator to authorize and revoke his delegation of decryption rights dynamically and offers more flexible access control on externally stored encrypted data. Definition and security model of single-hop directly revocable AB-CPREs are given, and the first detailed construction of single-hop directly revocable AB-CPREs based on standard LWE assumptions is also proposed.